2021
DOI: 10.1016/j.foodchem.2020.128387
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of salmon: Influence of processing and intestinal conditions on macronutrients digestibility

Abstract: Salmon is the main dietary source of omega-3 lipids and contains high-biological value protein. However, processing techniques could affect macronutrient digestibility. Also, altered intestinal conditions, particularly given in pancreatic insufficiency, could threaten digestibility. This study tested both hypotheses by subjecting raw, marinated and microwave-cooked salmon to static in vitro digestion under healthy (pH 7, bile concentration 10 mM) and altered (pH 6, bile 1 or 10 mM) intestinal conditions with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Protein digestibility can be used to determine the rate and extent of protein digestion in food protein and is one of the most critical attributes to determine the nutritional characteristics of food [39] . Proteins with a high digestibility rate are more likely to be digested and absorbed by the body.…”
Section: Resultsmentioning
confidence: 99%
“…Protein digestibility can be used to determine the rate and extent of protein digestion in food protein and is one of the most critical attributes to determine the nutritional characteristics of food [39] . Proteins with a high digestibility rate are more likely to be digested and absorbed by the body.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of CD and CT in the digested diet were determined according to a previously reported method with slight modifications (Bolea et al, 2019). Briefly, 200 µL supernatant were diluted in 2 mL 2propanol, then the mixture was centrifuged at 16 200 g under 4 °C for 5 min.…”
Section: Determination Of Conjugated Diene and Trienementioning
confidence: 99%
“…Nevertheless, lipid oxidation does not only occur before consumption, and the possible oxidation and degradation of lipid during gastrointestinal digestion cannot be ignored (Nieva‐Echevarria et al ., 2020). Previous studies showed that a variety of foods, such as red meat (pork and beef), white meat (chicken and turkey), sea foods (salmon and clam), vegetable oils (corn, olive, sunflower and flaxseed oils) and marine oils (cod liver oil, anchovies, krill and algae oils) undergo lipid oxidation after simulated digestion in vitro (Kuffa et al ., 2009; Nieva‐Echevarria et al ., 2019; Tullberg et al ., 2019; Alberdi‐Cedeño et al ., 2020a,b,c; Goethals et al ., 2020; Sobral et al ., 2020; Asensio‐Grau et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the type of macronutrients, such as the chain length of fatty acids and the structures of protein, and the physical property of food matrix structure, which is the 3D structure in which macronutrients interact and assemble within the food, could all affect digestion of foods. These complex properties of macronutrients could thus influence digestion and glycemic responses in various ways [56][57][58]. In summary, fat and protein content of a meal might impact PP blood glucose and should be captured by assessment tools and integrated within the calculation of appropriate insulin dosing strategies.…”
Section: Determining How the Macronutrient Composition Of Meals Effects Glycemic Control In Pwdmentioning
confidence: 99%